Prophylactic endoscopic pylorus dilatation prior to esophagectomy for esophageal cancer to prevent delayed gastric emptying, study protocol for a placebo-controlled randomized trial (PROPPER trial) - C. Mann; F. Berlth; V. J. Lozanovski; M. Passalacqua; E. Hadzijusufovic; E. Uzun; G. Capovilla; M. Valmasoni; H. Lang; P. P. Grimminger (Trials)
Abstract Introduction Delayed gastric emptying (DGE) due to pyloric dysfunction remains a common postoperative complication after esophagectomy for cancer and can lead to severe secondary complications. As shown in a retrospective study, prophylactic EPBD performed 1 day before surgery can reduce the rate of postoperative DGE by reducing pyloric resistance. The objective of this study is to analyze the effect of prophylactic EPBD on postoperative DGE rates in patients receiving minimally invasive esophagectomy for cancer by gastric pull-up. Methods This study is designed as a multicenter randomized controlled trial (RCT) including patients with esophageal cancer or cancer of the gastroesophageal junction (adenocarcinoma and squamous cell carcinoma, with or without neoadjuvant treatment) scheduled for minimally invasive esophagectomy with gastric pull-up. After randomization, patients will either receive preoperative EPBD or a sham intervention in the routine preoperative endoscopy performed 1 day before surgery. The primary endpoint of this study will be rates of DGE, particularly those resulting from pyloric dysfunction, requiring intervention. Secondary outcomes will be major and minor postoperative complication rates, in-hospital mortality, adverse events during gastroscopy, length of ICU and hospital stay as well as postoperative pain and quality of life. In order to detect a difference between both groups at a two-sided 5% significance level, to achieve a power of 0.8 with a calculated dropout rate of approximately 20%, a sample size of 118 patients with 59 patients in every study arm will be needed. Discussion The presented PROPPER trial is the first multicenter RCT that will provide evidence regarding the efficacy of preoperative EPBD in reducing DGE after minimally invasive esophagectomy for cancer. Trial registration This trial was registered in the German Clinical Trials Register (DRKS), under the identifier DRKS00034360. Registered on May 29, 2024. The WHO trial registration data set can be found here: http://drks.de/search/en/trial/DRKS00034360 .